Determining the effect of malondialdehyde on the IgE‐binding capacity of shrimp tropomyosin upon in vitro digestion. (17th May 2017) - Lv, Liangtao; Lin, Hong; Li, Zhenxing; Ahmed, Ishfaq; Chen, Guanzhi
Abstract: BACKGROUND: Stability in simulated gastric fluids is considered an important parameter for the estimation of food allergenicity. Moreover, proteins in food are highly susceptible to lipid oxidation during processing and preservation. In this study, the change in the IgE‐binding capacity of malondialdehyde (MDA)‐treated shrimp tropomyosin (TM) following in vitro digestion was investigated by SDS‐PAGE and western blot. RESULTS: Shrimp TM treated with different concentrations of MDA was slightly degraded and became increasingly resistant to pepsin digestion over time. While untreated TM was rapidly degraded, MDA‐treated TM showed some resistance and was degraded by trypsin only after increasing the digestion time. Results of immunoblotting studies on IgE using sera from patients allergic to shrimp indicated that the IgE‐binding capacity of TM and MDA (50 mmol L −1 )‐treated TM decreased slightly after pepsin digestion and significantly decreased after trypsin digestion. CONCLUSION: The study indicated that the resistance of TM to degradation increased after oxidation. The treatment with proteases, especially trypsin, is quite effective in decreasing the IgG/IgE‐binding capacity of shrimp TM. © 2017 Society of Chemical Industry